A Systematic Literature Review on the Use of AI to Improve Management-Supplier Relationships - Titi Hardiyati; I Made Surya Negara Sudirman (PT. Global World Scientific, 2026)
The application of Artificial Intelligence (AI) in improving Supplier Relationship Management (SRM) is crucial. Although there is extensive research on AI applications, efforts to systematically review this specific research topic present a challenge because many initiatives have failed to improve supplier relationship management through the use of AI. Therefore, this study aims to conduct a systematic literature review focused on the transformative role of AI in fostering collaboration, transparency, and efficiency across the modern supply chain. The review process encompasses three main methodological steps: the review framework, the formulation of research questions, and a systematic data search strategy (identification, screening, eligibility assessment, quality assessment, as well as data extraction and analysis). Drawing insights from 12 (twelve) research articles, this review highlights the significant contributions of AI-based technologies—such as predictive analytics, natural language processing, and machine learning—to supplier selection, communication, risk management, and real-time feedback. These findings underscore AI’s capacity to enhance trust and adaptability through adaptive decision-making and data-driven strategies, enabling personalized approaches and robust relationship management. While significant progress is evident, challenges such as technology adoption, integration complexity, and the digital divide remain.